(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article presents a theoretical and analytical review of the impact of functional training on the physical and psycho-emotional state of students in non-specialized groups at higher education institutions. Current trends in the decline of physical activity under conditions of educational digitalization and increasing academic workload are examined. The physiological mechanisms of adaptation to complex physical loads are analyzed, including neuromuscular regulation, autonomic balance, and stress response processes. The characteristics of functional training are considered as an integrative form of physical activity that simultaneously develops strength endurance, coordination abilities, and overall work capacity. Its role in preventing hypodynamia, postural disorders, and psycho-emotional tension among students is substantiated. The study concludes that incorporating functional training into university physical education programs is advisable as an effective means of strengthening health, enhancing adaptive capacity, and fostering sustainable motivation for regular physical activity.